(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
COVID-19 vaccinations have been associated with irregularities in the menstrual cycle and symptoms occurring pre and post-menstruation, affecting women’s reproductive health. This study aimed to demonstrate the impact of COVID-19 vaccines on women’s reproductive health by examining the association between COVID-19 vaccines and disturbed menstrual cycles. This cross-sectional survey-based study was conducted among adult females at King Saud University, Saudi Arabia, from April 2022 to August 2022. A total of 380 participants were selected through a stratified random sampling technique. Ethical approval was obtained from the Deanship of Scientific Research at King Saud University. The data were analysed using descriptive statistics and appropriate statistical tests. The results revealed that 53.9% of the participants experienced disturbances in the menstrual cycle after receiving the COVID-19 vaccination. Adult females aged 18-25 showed the highest rate of disorders. Menstrual disruptions were substantially correlated with marital status (p = 0.05), with a significant association between the number of COVID-19 vaccine doses and the occurrence of menstrual disturbances (p = 0.001). The administration of the vaccination during menstruation was linked to a notable occurrence of menstrual disturbances, although the p-value showed no statistical significance. A significant correlation was examined (p < 0.05) between pre-existing menstrual problems and the occurrence of disorders after receiving the COVID-19 vaccine (p < 0.05). The study emphasised the importance of tailored healthcare treatments for women following COVID-19 vaccination and the need for regular evaluation of reproductive health outcomes post-COVID-19 vaccination.